Pengaruh Digital Marketing dan Word of Mouth terhadap Keputusan Pembelian Pada Blibli di Kota Batam - Siagian, Setia Oktavia; Haldy, Muhammad (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The development of digital technology has significantly transformed consumer behavior, particularly in purchasing activities that have shifted from conventional methods to digital systems. This transformation has also impacted the cosmetics industry, where products are increasingly marketed through e-commerce platforms. Factors such as ease of access, time efficiency, and convenience in online shopping have made e-commerce a primary choice for consumers. In this context, digital marketing plays a crucial role in reaching and influencing consumers through various digital channels, including social media, search engines, and digital content. In addition, word of mouth contributes to shaping consumer perceptions based on experiences and recommendations shared by other users. Purchasing decisions result from consumers’ evaluation processes that consider product quality, price, brand image, and perceived benefits. This study aims to examine the influence of digital marketing and word of mouth on purchasing decisions for cosmetic products on the Blibli e-commerce platform. A descriptive quantitative research design was employed, with the study conducted in Batam City. Data were collected through an online questionnaire and analyzed using SPSS, including validity testing, reliability testing, t-tests, and analysis of variance (ANOVA). The findings of this study are expected to provide insights for businesses in developing effective digital marketing strategies to enhance consumer purchasing decisions in the e-commerce sector.